2019
DOI: 10.3389/fncel.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Evaluation of Photoreceptor Synapses in Developing, Degenerating and Regenerating Retinas

Abstract: Quantitative and qualitative evaluation of synapses is crucial to understand neural connectivity. This is particularly relevant now, in view of the recent advances in regenerative biology and medicine. There is an urgent need to evaluate synapses to access the extent and functionality of reconstructed neural network. Most of the currently used synapse evaluation methods provide only all-or-none assessments. However, very often synapses appear in a wide spectrum of transient states such as during synaptogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…In isolation, these do not prove the formation of a true synapse, and indeed we do not know whether a human/mouse synapse would look similar to a homotypic synapse of either species, but they do strongly indicate an attempt to form a putative synaptic contact. Although others have shown pre-synaptic staining, the only other reports of proximity of pre- and post-synaptic markers are those by Mandai and colleagues ( Akiba et al., 2019 ; Mandai et al., 2017 ) involving the homotypic transplantation of murine sheets. Our study is the first to show the potential to form functional heterotypic human cone/mouse BC connections.…”
Section: Discussionmentioning
confidence: 99%
“…In isolation, these do not prove the formation of a true synapse, and indeed we do not know whether a human/mouse synapse would look similar to a homotypic synapse of either species, but they do strongly indicate an attempt to form a putative synaptic contact. Although others have shown pre-synaptic staining, the only other reports of proximity of pre- and post-synaptic markers are those by Mandai and colleagues ( Akiba et al., 2019 ; Mandai et al., 2017 ) involving the homotypic transplantation of murine sheets. Our study is the first to show the potential to form functional heterotypic human cone/mouse BC connections.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that we were unable to observe differences in connectivity due to the large sample variation, or alternatively it may be that although the number of synapses is similar, the quality, i.e. the strength of synaptic connectivity 20 or the distribution of synapse across rosettes differs. Although we are uncertain of the underlying mechanism, reduction in aberrant RGC activity seems to substantially improve the performance after transplantation.…”
Section: Discussionmentioning
confidence: 92%
“…We have often seen images indicative of robust neural integration, such as in Figures 3a-b, with host bipolar dendrites extending towards graft cells and surrounded by photoreceptor presynaptic marker RIBEYE 20 . It is, however, difficult to confirm bona fide synapses formed between host bipolar cells and graft photoreceptor cells (hereinafter referred to as “ de novo ” synapse), as graft bipolar cells may also form synapses.…”
Section: Resultsmentioning
confidence: 98%
“…Further, changes in synaptic proteins indicate that synaptogenesis in the IPL and OPL is active during D20–D30. Plexiform layers in mice in vivo start to develop around P5, photoreceptor bipolar synapse start to form at about P7, and synaptogenesis is complete at about P21 ( Akiba et al, 2019 ). Supporting our earlier studies showing that all retinal cell types are generated, the synapse data also suggest that although an IPL forms, the inner retina is not yet well developed at D20, and that this might not improve upon extended culture.…”
Section: Resultsmentioning
confidence: 99%
“…Synaptic integration of neurons is a key process during retinal maturation and in gaining visual function. This integration is completed in the mouse in vivo at about P21 ( Akiba et al, 2019 ). Here, we observed that synaptogenesis occurs in parallel to POS formation in the trisection-based MRO system, which is supported by temporal changes in synaptic-protein and gene expression.…”
Section: Discussionmentioning
confidence: 99%